Long-read single-cell sequencing using scCOLOR-seq - Philpott, M; Oppermann, U; Cribbs, AP (Humana Press, 2023)
Single-cell sequencing allows for the measurement of sequence information from individual cells with next-generation sequencing (NGS). However, its application to third-generation sequencing platforms such as Oxford Nanopore has been challenging because of its lower basecalling accuracy. Here we describe the method to perform highly accurate single-cell COrrected Long-Read sequencing (scCOLOR-seq) by droplet-based encapsulation of cells and sequencing using the Oxford Nanopore Sequencing system.